Correlates of knowledge on birth defects and associated factors among antenatal mothers in Galle, Sri Lanka: a cross-sectional analytical study - Janithra De Silva; Sujeewa Amarasena; Kapila Jayaratne; Bilesha Perera (BMC, 2019)
Abstract Background Birth defects (BD) are considered a leading cause of childhood morbidity and mortality. Personal, cultural, and health care system barriers may increase the incidence of BD in low and middle income countries. In this study we assessed the knowledge of antenatal mothers on BD, associated factors, and prevention and management. Methods Three hundred and fifty (350) antenatal mothers were surveyed using a pretested, self-administered questionnaire. The knowledge on BD was evaluated under 3 categories; knowledge on BD, knowledge on associated factors, and knowledge on prevention and management. The total scores were calculated for each category and converted into percentages. A higher percentage score indicates a high level of knowledge. Descriptive statistics and regression models were used for data analysis. Level of significance was considered as p < 0.05. Results Mean age of the participants was 28.7 years (SD = 5.2). The age range was 17-44 years. Most of the participants (79%) had studied up to secondary or tertiary education. The average scores of knowledge on BD, associated factors, and prevention and management of BD were 57.6% (95% CI = 52.3-62.9%), 55.1% (95% CI = 49.8-60.4%) and 58.8% (95% CI = 53.5-64.1%) respectively. The average score on the overall total knowledge was 56.4% (95% CI = 51.1-61.7%). Mother's level of education, monthly income of the family and number of clinic visits made by the mother were found to be positively associated with the overall knowledge. About 62% of the participants had taken folic acid (FA) preconceptionally, a major preventive factor of BD associated with the nervous system. Folic acid intake was positively associated with age and educational level, but negatively associated with parity. Media (36.9%) and Public Health Midwives (PHMs) (20%) were found to be the major sources of knowledge on BD, associated factors and prevention in this target group. Conclusions The average overall knowledge on BD in this group of antenatal mothers was moderate. Thus, there is a need to improve the knowledge in eligible women to reduce the occurrence of BD, ideally before they become pregnant. Media and PHMs were seem to be the effective and possible resources that can be used to educate the community on BD, associated factors and prevention of BD in Sri Lanka.